Factors That Facilitate Regulatory Approval for Drug-Device Combination Products in the European Union and United States of America: A Mixed Method Study of Industry Views. (July 2018) - Masterson, Fiona
Background: The regulatory environment is one of the key factors in successfully bringing an innovative medical product, like a drug-device combination product, to market. This paper offers insight into the experiences of those involved in obtaining regulatory approval of drug-device combination products in the European Union and the United States. Methods: The research consisted of two phases, qualitative data collection (through semi-structured interviews) and analysis, followed by quantitative data collection (through an online survey) and analysis. Results: A conceptual model was developed that depicted the facilitating factors for obtaining regulatory approval of a drug-device combination product, relevant to the European Union and United States systems, respectively. Conclusions: This model provides, for the first time, a comprehensive understanding of these factors, providing a foundation that could be adapted to reflect specific drug-device combination products. This research demonstrated originality of approach in interviewing thought leaders in the life sciences sector as well as conducting a survey that spans two of the largest jurisdictions for drug-device combination products in the world.